ASSESSMENT OF THE IMPORTANCE OF TRAINING IN THE DEVELOPMENT OF STRENGTH AND QUICK-STRENGTH QUALITIES OF SKILLED WRESTLERS - Jamshidbek S. Ergashev (Western European Studies, 2024)
Special exercises are used to develop the strength and quick-power qualities of skilled wrestlers. In this article, the universal dynamographic stand (UDS) was used in monitoring quality development. The obtained data allow us to determine the parameters of the development of strength and quick-strength qualities among qualified wrestlers
Keywords: wrestling; strength and quick-strength exercises; set of exercises